(untitled) (Journal of Informatics and Mathematical Sciences, 2009)
This paper is considered with modelling and analysis of a two identical unit standby system with the concept of rest of the operator cum repairman. Here, the concept of correlation between busy time and idle time of the operator cum repairman is considered which is not, generally, seen in the literature. If the repairman is not able to repair a failed unit within a specified time limit (pre fixed) then the failed unit is replaced by a replacement facility. The different measures of economic importance are obtained by using regenerative point technique. The MTSF and profit function have also been studied through graphs in respect of various parameters in a particular case when repair time distribution is taken as exponential.